If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -3 = 3 + 6y Reorder the terms: -3 + 7y = 3 + 6y Solving -3 + 7y = 3 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -3 + 7y + -6y = 3 + 6y + -6y Combine like terms: 7y + -6y = 1y -3 + 1y = 3 + 6y + -6y Combine like terms: 6y + -6y = 0 -3 + 1y = 3 + 0 -3 + 1y = 3 Add '3' to each side of the equation. -3 + 3 + 1y = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 1y = 3 + 3 1y = 3 + 3 Combine like terms: 3 + 3 = 6 1y = 6 Divide each side by '1'. y = 6 Simplifying y = 6
| 5/7x*r=500 | | X=170+-3x | | (Z)(z)-182=450 | | (x+4)(x+3)(x-15)=0 | | 5/8x20 | | 2u+12=20 | | y=100-3(4) | | t+-16=-24 | | 12.5y+3+18+-9.25y= | | 0.7x-1.4=1.9x+1.5 | | 10=2v-10 | | 9/10x25/6 | | 16x+2x=18 | | 8n+16.2=1 | | B+1.5-.4-5.72=2.3b-1.5 | | 3-.23b=.34b-7 | | 7b+1=6b+6 | | (8x-5)(2x+4)=0 | | 36=9(x-7) | | 5(a+3)+2=2m+5 | | 5v+13=73 | | 20p-4(6p-12)=8(6p-12)-16p | | 17y^2-14y=0 | | 15k^2/6k-9 | | -2.5(2x+6)=3x-6x | | 6(x-7.2)=4.2 | | X^2+22x-54=0 | | 8(3n-1)=(9n+6)+4 | | 1/6(-3x-2) | | x+14+19=40 | | 20logk=10 | | X+3x+10=180 |